Emotional and cognitive influences on alcohol consumption in middle-aged and elderly Tanzanians: a population-based study - Liu, Shuyan; Kazonda, Patrick; Leyna, Germana H.; Rohr, Julia K.; Fawzi, Wafaie W.; Shinde, Sachin; Abioye, Ajibola Ibraheem; Francis, Joel M.; Probst, Charlotte; Sando, David; Mwanyka-Sando, Mary; Killewo, Japhet; et al. (Scientific reports, 2024)
Alcohol consumption in Tanzania exceeds the global average. While sociodemographic difference in alcohol consumption in Tanzania have been studied, the relationship between psycho-cognitive phenomena and alcohol consumption has garnered little attention. Our study examines how depressive symptoms and cognitive performance affect alcohol consumption, considering sociodemographic variations. We interviewed 2299 Tanzanian adults, with an average age of 53 years, to assess their alcohol consumption, depressive symptoms, cognitive performance, and sociodemographic characteristics using a zero-inflated negative binomial regression model. The logistic portion of our model revealed that the likelihood alcohol consumption increased by 8.4% (95% confidence interval [CI] 3.6%, 13.1%, p < 0.001) as depressive symptom severity increased. Conversely, the count portion of the model indicated that with each one-unit increase in the severity of depressive symptoms, the estimated number of drinks decreased by 2.3% (95% CI [0.4%, 4.0%], p = .016). Additionally, the number of drinks consumed decreased by 4.7% (95% CI [1.2%, 8.1%], p = .010) for each increased cognitive score. Men exhibited higher alcohol consumption than women, and Christians tended to consume more than Muslims. These findings suggest that middle-aged and elderly adults in Tanzania tend to consume alcohol when they feel depressed but moderate their drinking habits by leveraging their cognitive abilities.
Gesehen am 22.09.2025